9514 1404 393
Answer:
(x, y) = (-4, -6)
Explanation:
For graphing by hand, it can be convenient to put the equations in slope-intercept form. Multiplying the first equation by -2 gives ...
y = -x -10
The second equation is already in slope-intercept form.
These equations tell you ...
y = -x -10 . . . the slope is -1 and the y-intercept is -10. It goes up to the left from -10 on the y-axis
y = 2x +2 . . . the slope is 2 and the y-intercept is 2. It goes down to the left from +2 on the y-axis.
The solution to the system is (-4, -6).